The Quality of Parent-Child Relationships among Delinquent Female Adolescents in Kuala Lumpur - Jaafar, Juliana Rosmidah (2005)
The main objective of this study is to explore the quality of parent-child relationships among delinquent female adolescent (DFA) school students. Specifically, the study compared DFAs’ perceptions of father-daughter and mother-daughter relationships on three parent-child relationship variables, namely: (1) parent-child attachment; (2) parent-child supervision; and (3) parentchild communication. Each variable was studied separately for mothers and fathers. This study also examined the relationship between respondents’ selected background characteristics (number of siblings, parents, education level and monthly family income) with delinquency scores. Significant predictor variables were also identified. Seven null hypotheses were tested. Respondents were 94 Form One DFA school girls from five Keramat District secondary schools in Kuala Lumpur. The DFAs were selected based on school discipline records and through referrals by school counselors. Parent-child attachment was measured using the Inventory of Parent and Peer Attachment (Armsden and Greenberg, 1987). Parental supervision was measured using a modified version of the Strictness / Supervision Scale by Dutra and Chance (1997). Parent-child communication was measured using a combination of items from the Self-Report Instrument (Beavers, Hampson and Hulgus, 1985) and Parent-Child Relationship Survey (Fine, Moreland and Schwedel, 1983). Respondents level of involvement in delinquent acts were scored using a delinquency scale developed by Rozumah, Abdullah Al-Hadi, Rumaya, Asnarulkhadi, Amna, Mansor and Tan (2003). Descriptive analyses show that DFAs have average academic achievement. Their parents’ level of education was also average. Only 4.3% had university level education. Majority (97.9%) of the fathers and half of the mothers are working. Most families (38.3%) have family income above RM2000 per month while only 7.4% have incomes equal to or less than RM500. The level of delinquent acts scores were low but presented a worrying trend. Results revealed that DFAs were involved in a variety of delinquent acts within and outside the school compound such as smoking, carrying weapons to school, drunken behavior in public, obscene behavior, and gangsterisme. Results revealed significant differences between DFAs perceptions of father-child and mother-child relationship on all three variables, namely: (i) mother-child attachment (mean score=75.55) and father-child attachment (mean score= 73.08 ), t=2.62, p<0.01; (ii) mother-child supervision (mean score= 35.37) and father-child supervision (mean score=33.38) , t=4.88, p<0.001; and (iii) mother-child communication (mean score= 29.98) and father-child communication (mean score=27.37), t=4.69, p<0.001. DFAs perceived that the quality of their mother-child relationship were better than their father-child relationship in terms of respect, trust, readiness to share problems, supervision of activities inside and outside their homes, confidence in communication to solve problems as well as openness in communication. Results also show that only family income had a significant and negative correlation with delinquency scores, r = -.36, p<0.05, while only mother-child communication was found to be a significant predictor variable contributing 16.6% to the variance. Results indicate that the three parent-child relationship variables studied are influential in preventing early adolescent girls from involvement in delinquency. Hence, female delinquency prevention programmes need to focus on improving parent-child relationships. Future research should examine parent-child relationships among pre-adolescents and later adolescents, as well as compare respondents on variables such as gender, school type, rural-urban locations, ethnicity, and family structure.